2021
DOI: 10.1111/ajes.12370
|View full text |Cite
|
Sign up to set email alerts
|

Neoliberalism and the Crisis in Higher Education: The Cost of Ideology

Abstract: A number of factors have contributed to the crisis in higher education, including the long‐term transformation in funding. In this article, I argue that neoliberalism can explain many of the processes leading to our changing commitment to colleges and universities and the cost increases that this change has produced. A number of neoliberal assumptions firmly rooted in conventional wisdom have contributed to a “student‐as‐customer” phenomenon, which is, itself, a cost driver. I look at the development of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 36 publications
(35 reference statements)
0
48
0
8
Order By: Relevance
“…Doctoral students are in training to learn how to create knowledge, and the role they play in the knowledge economy calls into question how they are viewed by the degree-offering institutions as well as the societies they enter into upon completion of their terminal degree. From the perspective of doctoral students, tuition costs are on the rise across the board among American colleges and universities, and Mintz (2021) argues the rising costs are in part due to a general adoption of neoliberal policies and politics that suggest education is a private good. Mintz writes, "Although the potential for personal gain is far from new, in the last few decades, the view of education as a private good and the neoliberal corollary that emphasizes individual responsibility and individual consequences have increasingly framed the discourse of education policy" (p. 84).…”
Section: Doctoral Educationmentioning
confidence: 99%
“…Doctoral students are in training to learn how to create knowledge, and the role they play in the knowledge economy calls into question how they are viewed by the degree-offering institutions as well as the societies they enter into upon completion of their terminal degree. From the perspective of doctoral students, tuition costs are on the rise across the board among American colleges and universities, and Mintz (2021) argues the rising costs are in part due to a general adoption of neoliberal policies and politics that suggest education is a private good. Mintz writes, "Although the potential for personal gain is far from new, in the last few decades, the view of education as a private good and the neoliberal corollary that emphasizes individual responsibility and individual consequences have increasingly framed the discourse of education policy" (p. 84).…”
Section: Doctoral Educationmentioning
confidence: 99%
“…In the same way, we found that ELT education programs should reconsider how they are structuring academic spaces for language teaching and teaching practicum, avoiding the spread of ideologies that promote 3 In Colombia, the Ministry of National Education (MEN in Spanish) has established the criteria for granting high-quality accreditation to universities or specialties. These criteria respond to a neoliberal policy established in university education with which entering the world university rankings is intended and thus being part of the world market for higher education (Mintz, 2021;Olsen & Peters, 2005).…”
Section: Stories That Trigger My Interest In Pre-service English Language Teachers' Experiences In Initial Teacher Educationmentioning
confidence: 99%
“…Political dynamics are shifting as well toward greater accountability and less state funding for higher education institutions (Kelchen, 2018;Macheridis & Paulsson, 2021). Costs of attendance continue to rise as state allocations for higher education shrink, all the while federal and state legislators echo public cries for higher accountability placed on institutions to produce more workforce-ready graduates (Mintz, 2021;Mitchell et al, 2017;Umbricht et al, 2017). Possibly as a side effect of astronomical costs of attendance and a collectively perceived underwhelming return on investment, public ideological perception of the value of higher education has taken a hit (Bowen, 1996;Mintz, 2021).…”
Section: Introductionmentioning
confidence: 99%